Post-9/11: Making Islam an American Religion - Haddad, Yvonne Yazbeck (Religions, 2014)
This article explores several key events in the last 12 years that led to periods of heightened suspicion about Islam and Muslims in the United States. It provides a brief overview of the rise of anti-Muslim and anti-Islam sentiment known as “Islamophobia”, and it investigates claims that American Muslims cannot be trusted to be loyal to the United States because of their religion. This research examines American Muslim perspectives on national security discourse regarding terrorism and radicalization, both domestic and foreign, after 9/11. The article argues that it is important to highlight developments, both progressive and conservative, in Muslim communities in the United States over the last 12 years that belie suspicions of widespread anti-American sentiment among Muslims or questions about the loyalty of American Muslims. The article concludes with a discussion of important shifts from a Muslim identity politics that disassociated from American identity and ‘American exceptionalism’ to a position of integration and cultural assimilation.